Implikasi Pendidikan dari Novel Negeri 5 Menara Karya Ahmad Fuadi pada Pendidikan Moral - Santi Susanti (UNISBA Press, 2022)
Abstract. Some of the moral education in today's society is no longer in accordance with the prevailing norms. In order for moral formation, education is needed. Morals will not be formed if no one provides education. With moral education, norms will be formed which are determined in the place where he was born. Education can be taught through formal educational institutions and non-formal education. In addition, education can be applied and instilled in various ways, one of which is by reading novels. By reading novels, it will increase the knowledge of readers, increase knowledge for readers, increase knowledge and order of language. This study aims to describe the values ​​of moral education contained in the novel Negeri 5 Menara, to describe the essence of moral value education from the novel Negeri 5 Menara, to describe the views of education experts on educational morals, and to describe the assessment of the basic education moral novels at Negeri 5 Menara towards PAI learning. In this research, it is a qualitative descriptive. The data were analyzed using a qualitative description technique, namely a research procedure by presenting the data in the form of an analysis of the results of moral values ​​in the novel Negeri 5 Menara. The results show that the form of moral values ​​contained in the novel Negeri 5 Menara includes: the form of moral values ​​has three types, namely the first form of moral values ​​in human relations with God has variants in the form of praying to God, belief, gratitude, trustworthiness, and sincerity. The form of moral values ​​in human relations with oneself has variants of unyielding, determination and hard work. While the form of moral values ​​in human relations with other humans is advice, respect for parents, motivation, honesty, friendship, sympathy, compassion, and empathy. Abstrak. Pendidikan moral yang berada dalam lingkungan masyarakat saat ini sebagian sudah tidak sesuai dengan norma-norma yang berlaku. Agar terbentuknya moral, diperlukan pendidikan. Moral tidak akan terbentuk jika tidak ada yang memberikan pendidikan. Dengan pendidikan moral akan terbentuk norma-norma yang sudah ditentukan di tempat ia dilahirkan. Pendidikan dapat diajarkan melalui lembaga pendidikan formal dan pendidikan nonformal. Selain itu Pendidikan dapat diterapkan dan ditanamkan dengan berbagi cara, salah satunya yaitu dengan membaca novel. Dengan membaca novel, hal itu akan menambah pengetahuan pada pembaca, berfikiran terbuka bagi para pembacanya, menambah kreativitas dan memperkaya tatanan bahasa. Penelitian ini bertujuan untuk mendeksripsikan nilai-nilai pendidikan moral yang terkandung dalam novel Negeri 5 Menara, mendeskripsikan esensi pendidikan nilai moral dari novel Negeri 5 Menara, dan mendeskripsi implikasi dari esensi nilai pendidikan moral novel Negeri 5 Menara terhadap pembelajaran PAI. Dalam peneliatian ini merupakan Penelitian ini menggunakan pendekatan kualitatif, yaitu pendekatan deskriptif analisis, dan menggunakan metode penelitian kepustakaan (literatur). Hasil penelitian menunjukan wujud nilai moral yang terdapat dalam novel Negeri 5 Menara meliputi: wujud nilai moral memiliki tiga jenis yakni yang pertama wujud nilai moral dalam hubungan manusia dengan Tuhan memiliki varian yang berupa berdoa kepada Tuhan, keyakinan, bersyukur, tawakal, dan ikhlas. Wujud nilai moral dalam hubungan manusia dengan diri sendiri memiliki varian pantang menyerah, tekad dan kerja keras. Sedangkan wujud nilai moral dalam hubungan manusia dengan manusia lain terdapat nasihat, hormat kepada orang tua, motivasi, jujur, persahabatan, simpati, kasih sayang, dan empati.